Effective Promotion Strategy of Integrated Islamic Education Institutions in Modern Society - Riyadi, Slamet; Darwis, Muhammad; Judijanto, Loso; Nicolas, Djone Georges; Saefudin, Arif (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Education is considered a service product produced by non-profit educational institutions to show the results of the educational process. This research aims to determine the management promotion strategy to compete with other Islamic educational institutions in modern society. This research focuses on Al-Fityan School Medan, North Sumatra, a leading Islamic school comprising RA, SDIT, SMPIT, and SMAIT. This research uses a qualitative approach with a case study type, with data collected through interviews, observation, and documentation. The data analysis process began when the researcher arrived at the research location; after the data was collected, the analysis was carried out through data conditioning, data presentation, and conclusion drawing. The results showed that the concept of competitive promotion management in this institution includes excellent programs, the idea of a strong determination to carry out worship, the idea of mastering global languages, and the idea of improving skills, especially in science and technology. The implications include the potential for developing an integrated Islamic education promotion strategy. The findings also open up opportunities for further research in education management and competitive promotion.